Protecting Emergency Responders Lessons Learned from Terrorist Attacks - Jackson, Brian A. (RAND Corporation, 2002)
In December 2001, a conference held in New York City brought together individuals with firsthand knowledge of emergency responses to terrorist attacks to discuss ways to improve the health and safety of emergency workers who respond to large-scale disasters. The meeting considered the responses to the September 11, 2001 attacks at the World Trade Center and the Pentagon and the 1995 attack at the Alfred P. Murrah Federal Building in Oklahoma City, Oklahoma, as well as the emergency responses to the anthrax incidents that occurred through Autumn 2001. This book is intended to help managers and decisiomakers understand the unique working and safety environment associated with terrorist incidents, understand the equipment needs of emergency workers, and improve education and training programs and activities directed at the health and safety of emergency responders.